1985
DOI: 10.1093/nar/13.24.8827
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the human gene encoding the invariant γ-chain of class II histocompatibility antigens

Abstract: The primary structures of a cDNA and the genomic DNA of a gene selectively expressed in chronic lymphocytic leukemia were determined. A computer search of the nucleotide sequence data bank identified this gene as the invariant gamma-chain associated with class II histocompatibility antigens. The invariant gamma-chain genomic sequence spans about 11 kilobases, with eight exons and seven introns. Three of the introns contain members of the Alu repeat family. A putative cap site and promoter sequence were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…From this experiment, we concluded that clone p41-1 was derived from a mature mRNA, called p41 mRNA, which has the capacity to direct the synthesis of a protein related to the p33 In chain. p41 mRNA is the result of a differential splicing event Southern blot data and analysis of genomic clones have supported the existence of a single In chain gene (Kudo et al, 1985;and unpublished). From a comparison ofthe sequence of p41-1 cDNA with the In chain gene sequence published by Kudo et al (1985), we observed that the position corresponding to the boundary of the additional segment of clone p41-1 is precisely at the splice junctions between exon 6 and exon 7.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…From this experiment, we concluded that clone p41-1 was derived from a mature mRNA, called p41 mRNA, which has the capacity to direct the synthesis of a protein related to the p33 In chain. p41 mRNA is the result of a differential splicing event Southern blot data and analysis of genomic clones have supported the existence of a single In chain gene (Kudo et al, 1985;and unpublished). From a comparison ofthe sequence of p41-1 cDNA with the In chain gene sequence published by Kudo et al (1985), we observed that the position corresponding to the boundary of the additional segment of clone p41-1 is precisely at the splice junctions between exon 6 and exon 7.…”
Section: Resultsmentioning
confidence: 93%
“…p41 mRNA is the result of a differential splicing event Southern blot data and analysis of genomic clones have supported the existence of a single In chain gene (Kudo et al, 1985;and unpublished). From a comparison ofthe sequence of p41-1 cDNA with the In chain gene sequence published by Kudo et al (1985), we observed that the position corresponding to the boundary of the additional segment of clone p41-1 is precisely at the splice junctions between exon 6 and exon 7. Moreover, the complete sequence of the additional intervening segment of clone p41-1 was found in the sequence of the genomic clone within the intron separating exons 6 and 7, 1353 bp from the 3' end of exon 6 (Kudo et al, 1985; Figure 2B).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The GA733 genes are related to the HLA-DR-associated invariant chain gene (25,26), in that exon 6b of this gene (27) is homologous to the second type I repeat of thyroglobulin, and the second and fourth type I repeats derive from an ancestral 60-amino acid unit (24). The relationships among these three genes are depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%